2018
DOI: 10.1016/j.mmcr.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophyte infection caused by Nannizzia gypsea : A rare case report from Madagascar

Abstract: We report a rare case of dermatophyte infection of the glabrous skin (Tinea corporis) caused by Nannizzia gypsea (formerly Microsporum gypseum). A 22-year-old Malagasy female who reported close contact reportedly with cats, presented a single round lesion with a peripheral, active, squamous and pruriginous inflammatory bead. Morphologic species identification was confirmed by sequencing the internal transcribed spacer (ITS) region of the genome. Specific treatment with oral loratadine and topical miconazole cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 14 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The prevalence of infection rates is assessed at approximately 1% of all dermatophytoses, although in some regions it can reach up to 7% (Seebacher et al 2008;Jankowska-Konsur et al 2011;Vena et al 2012;Hubka et al 2015). This group of dermatophytes comprises a high and still rising number of species, which in part is related to the increasing use of molecular methods in species identification (Gnat et al 2019f, 2019e) Moreover, in the last few years, several presumed soil dermatophytes have been isolated from clinical material (Dolenc-Voljc and Gasparic 2017;Soankasina et al 2017;Gnat et al 2019a). Nonetheless, geophilic dermatophytes are regarded as rather opportunistic pathogens as well as keratinophilic fungi with ecological importance, since they are involved in keratin degradation (Ginter-Hanselmayer et al 2007;de Hoog et al 2017).…”
Section: Problems In Diagnosis and Treatment Of Dermatophytosesmentioning
confidence: 99%
“…The prevalence of infection rates is assessed at approximately 1% of all dermatophytoses, although in some regions it can reach up to 7% (Seebacher et al 2008;Jankowska-Konsur et al 2011;Vena et al 2012;Hubka et al 2015). This group of dermatophytes comprises a high and still rising number of species, which in part is related to the increasing use of molecular methods in species identification (Gnat et al 2019f, 2019e) Moreover, in the last few years, several presumed soil dermatophytes have been isolated from clinical material (Dolenc-Voljc and Gasparic 2017;Soankasina et al 2017;Gnat et al 2019a). Nonetheless, geophilic dermatophytes are regarded as rather opportunistic pathogens as well as keratinophilic fungi with ecological importance, since they are involved in keratin degradation (Ginter-Hanselmayer et al 2007;de Hoog et al 2017).…”
Section: Problems In Diagnosis and Treatment Of Dermatophytosesmentioning
confidence: 99%
“…Soankasina and colleagues described an interesting case of dermatophytosis of the smooth skin (tinea corporis) in a 22-year-old woman from the Madagascar region. A detailed medical history revealed that she probably contracted the infection through contact with free-living cats [89]. Infection with N. gypsea by contact with an infected animal has also been observed in a 2-year-old boy from Italy with signs of infection on the scalp [90].…”
Section: Discussionmentioning
confidence: 97%
“…Recently, an interesting case of Tinea incognito caused by N. gypsea was reported in a 22-year-old immunocompetent female from Madagascar with contact of cats and without any apparent contact with soil. The lesions were presented as solitary, round with circinate scaly plaques with well-defined erythematous lesions and peripheral active zone filled with small vesicles [ 19 ]. The present case also records a unique clinical presentation, which is in agreement with the previously described lesions caused by N. gypsea .…”
Section: Discussionmentioning
confidence: 99%